How Does Servant Leadership Affect Turnover Intention a Company? - Muzakki Muzakki; Asep Heryyanto (Universitas Prasetiya Mulya, 2023)
The food and beverage industry continues to experience positive and substantial development from year to year. Nonetheless, attrition rates range between 60% and 300%. This study investigates the relationship between servant leadership, affective organizational commitment, and turnover intention. In addition, this study seeks to examine the role of affective organizational commitment as a mediator between servant leadership and turnover intention. This study's sample consisted of 78 restaurant employees. The technique used for data analysis was Structural Equation Modeling Partial Least Square (SEM PLS). According to the findings of the study, servant leadership and affective organizational commitment had a significant negative impact on turnover intention. Lastly, affective organizational commitment can substantially and negatively moderate the effect of servant leadership on turnover intention.